Husband's Support and Anxiety Levels in Primigravida Mothers Facing Childbirth: A Cross-Sectional Study - Lumastari Ajeng; Satria Eureka Nurseskasatmata; Rita Yulifah (Universitas STRADA Indonesia, 2025)
Background: Anxiety is commonly experienced by mothers during childbirth, and spousal support is crucial in alleviating it. Purpose: This study aims to determine the correlation between husband’s support and anxiety levels in primigravida mothers. Methods: This quantitative study utilized a cross-sectional design with purposive sampling involving 30 primigravida mothers at Aminah General Hospital, Blitar. Data were collected using the Zung Self-Rating Anxiety Scale and a social support questionnaire. Results: The study found that 66.7% of participants experienced mild anxiety due to receiving strong support from their husbands. The Spearman correlation test showed a significant relationship (p = 0.000, r = 0.535). Conclusions: Husband’s support plays a significant role in reducing anxiety levels among primigravida mothers during childbirth, especially through emotional, informational, instrumental, and appraisal support.